Evaluation of segmental scleral buckling surgery for stage 4A retinopathy of prematurity in China - Zhong, Yusheng; Yang, Yating; Yin, Hong; Zhao, Mingwei; Li, Xiaoxin; Liang, Jianhong; Cheng, Yong (Frontiers in Medicine, 2022)
Aims To describe the long-term effect of scleral buckling (SB) surgery for stage 4A retinopathy of prematurity (ROP). Methods A retrospective chart review was conducted for patients with a diagnosis of stage 4A ROP who underwent SB between October 2010 and October 2021. Basic data were collected from patient charts, including gender, birth weight, gestational age at birth, disease stage, presence of plus disease, preoperative treatment [laser photocoagulation, intravitreal anti-vascular endothelial growth factor (VEGF) agent therapy, or a combination of both] and complications (vitreous hemorrhages), postmenstrual age at surgery, intraoperative combined treatment, and total length of follow-up. Retinal attachment status after surgery, postoperative complications (glaucoma, cataract), date and type of subsequent retinal surgeries (if performed), and refractive status 1 year after surgery were evaluated. The follow-up time after the first procedure was over 1 year. Results Six-two eyes from forty-eight patients met the inclusion criteria for this study. The initial reattachment rate was 93.5% (58/62 eyes), and the final reattachment rate was 100% after two procedures at the end of follow-up. The incidence of cataracts was 3.2% (2/62), with no eye subsequently needing lensectomy surgery. None of the patients developed glaucoma during the follow-up time. The average spherical equivalent refraction value for patients was −3.00 ± 2.51 D (−7.60 D to +2.75 D) 1 year after surgery. Conclusion SB, especially segmental buckling, which induces less myopia and does not require buckle removal, has the potential to provide a significant positive impact in the treatment of stage 4A ROP.